Identifying protons trapped in hematite photoanodes through structure–property analysis. Issue 4 (16th December 2019) - Liu, Yutong; Smith, Rodney D. L.
Abstract : Features in Raman spectra are found to correlate to the band structure and photoelectrochemical behavior across a series of hematite photoanodes. Analysis suggests the presence of iron vacancies caused by the trapping of interstitial protons. Abstract : Uncertainty regarding the nature of structural defects in hematite and their specific impacts on material properties and photoelectrocatalytic water oxidation inhibits their development as photoanodes. We perform structure–property analysis on a series of hematite films fabricated by annealing lepidocrocite films with varied temperatures, annealing times and atmospheres and find a gradient in the magnitude of a crystal lattice distortion by tracking the relative intensity of a formally Raman inactive vibrational mode. Structure–property analysis reveals that this feature in the Raman spectrum correlates to photocurrent density, semiconductor band positions, and the onset of photoelectrocatalysis. We propose that the onset of photoelectrocatalysis is linked to the location of defects that act as intraband recombination sites; an increase in the degree of structural distortion shifts these states towards the conduction band, thereby facilitating recombination. Analysis of the nature of the key Raman vibrations, X-ray diffraction patterns, and the synthetic conditions leads us to assign the distortion to iron vacancies that are induced by the trapping of protons within the crystal lattice. The ability to rapidly diagnose a specific structural defect will aid in the optimization of fabrication protocols for hematite photoanodes.